THE ESSENCE AND METHODS OF COERCION IN THE CATEGORIES OF PHYSICS (CRIMINAL-LEGAL ISSUES) - M. S. Greenberg (Правоприменение, 2018)
The Subject. The article is devoted to impact of coercion to the difference of legal statuses between law-obedient individuals and abusers.The purpose of the article is to identify the difference between the impact of coercion on law-obedient citizens and abusers.Methodology. The author uses theoretical analysis as well as legal methods including formal legal analysis and the method of social modeling.Results, scope of application. It is proved that a certain difference (in the categories of phys-ics) should exist between the legal status of law-obedient individuals and abusers there is a certain difference. Where there is no such difference, there is no place for coercion.Conclusions. The author comes to the conclusion that the essence of any punishment is the deprivation of certain benefits, which means the difference between the status of a person who did not conflict with the criminal law and those who entered into such a conflict. The magnitude of the difference depends on the severity of the crime.